Development of simulation based real-time traffic light scheduling system - Wang, Xiaoman (Nanyang Technological University, 2022)
This project aims to demonstrate a specific real-time traffic light scheduling strategy called Split Cycle Offset Optimization Technique (SCOOT). Since the predecessor of SCOOT is TRANSYT system, its optimization process is introduced on the basis of TRANSYT and implemented by code. A traffic network of streets around Marina Bay is developed in VISSIM to evaluate the performance of SCOOT, and another real-time traffic light scheduling strategy called Sydney Coordinated Adaptive Traffic System (SCATS) is used for comparison with SCOOT. In addition, COM interface of VISSIM is also taken advantage of to satisfy the demands of real-time dynamic adjustment of traffic signal timing. This thesis contains theoretical knowledge in the related transportation field, as well as experimental design and simulation results.